High-pressure metasediments in central Turkey: Constraints on the Neotethyan closure history - Pourteau, Amaury; Candan, O.; Oberhnsli, R. (American Geophysical Union, 2010)
The distribution of oceanic domains and continental blocks in Central Anatolia remains a challenge in understanding the Alpine geodynamic evolution of the Tethys realm. The consumption of a Neotethys oceanic branch at the Mesozoic-Cenozoic boundary welded the Central Anatolian Crystalline Complex in central Turkey and the Anatolide-Tauride Block in western Turkey, with the northerly Eurasian margin. Whether those two regions constituted a single or two distinct continental masses is still matter of debate. High-pressure metamorphism has been locally evidenced in the Afyon Zone, which was, however, defined as a greenschist-facies metamorphic zone of the Anatolide-Tauride Block. Since the Afyon Zone composes a metamorphic equivalent of a continental margin exposed far south of the Izmir-Ankara suture zone, this encouraged us to reevaluate its metamorphic evolution in order to better understand the relation between western and central Turkey. Our investigations reveal that the high-pressure minerals Fe-Mg-carpholite and glaucophane are present in the entire Afyon Zone, which we reconsider as a blueschist-facies zone. We additionally present a tectonic reconstruction, stripping off the postcollisional tectonics. It reveals that today's bending of the high-pressure belt is consistent with an Eocene collision of the Anatolide-Tauride Block around the southern edge of the Central Anatolian Crystalline Complex. We argue that the Central Anatolian Crystalline Complex and the Anatolide-Tauride Block were two distinct continental masses separated by a Neotethyan oceanic stripe, the closure of which engendered subduction-related metamorphism in the latter and arc volcanism and high-grade metamorphism in the former by late Cretaceous to early Cenozoic. Copyright © 2010 by the American Geophysical Union.